Triple-layered encapsulation of sensitive biomolecules into poly (ε-caprolactone) nanofibers using AC electrospraying - Asatiani, Nikifor; Křtěnová, Petra; Šimon, Pavel; Kunc, Štěpán; Mikeš, Petr (Journal of biomaterials science. Polymer edition, 2025)
The incorporation of sensitive bioactive substances such as proteins or DNA into nanofibers poses a significant problem due to the toxicity of most organic solvents. The main idea of this study is to use alternating current electrospraying to create a suspension consisting of polyvinyl alcohol (PVA) capsules containing a bioactive substance dispersed in a solvent system suitable for a water-insoluble biocompatible polymer. In this suspension consisting of PVA capsules and a chloroform/ethanol mixture, poly (ε-caprolactone) (PCL) was dissolved and spun by needle-free electrospinning. The result is a fibrous PCL structure in which PVA capsules containing the bioactive agent are integrated. The PVA capsules protect the bioactive substance from the organic solvents needed to dissolve the PCL. To verify the efficacy of the capsules' protection against chloroform, the green fluorescent protein was first encapsulated into the nanofibers, followed by horseradish peroxidase. Both molecules were shown to retain their bioactivity within the nanofibers.
Keywords: proteins; Capsules; encapsulation; zelené fluorescenční proteiny; Polyesters; Chloroform; křenová peroxidasa; Green Fluorescent Proteins; ethanol; Solvents; Nanofibers; Polyvinyl Alcohol; rozpouštědla; polyvinylalkohol; AC electrospraying; Biocompatible Materials; polyestery; nanovlákna; Horseradish Peroxidase; biomolecules; tobolky; biokompatibilní materiály; Ethanol; chloroform; electrospinning